From coast to forest : development of Icelandic coastal forests, their linkage to aquatic systems and the perspective of locals on them - Frank, Kerstin, 1985- (2020)
Coastal forests are not closed ecosystems, but are in constant interaction with other systems, including fresh waters and oceans. Interaction also takes place between humans and forests, as forests impact humans as much as humans impact forests. Therefore, a comprehensive approach is needed in order to understand ecological processes in forests and to manage them in a functional way that is also supported by society. This is especially important in Iceland, a mostly treeless country, where reforestation is an important subject on one hand, but on the other hand, there is a lack of studies on this topic. In this master’s thesis, two forest stands in the Westfjords of Iceland were studied by including a natural- as well as social-scientific approach. Within two 15 year old stands in Tálknafjörður, the growth and the survival of trees were analysed, as well as the CO2-sequestration potential. Furthermore, the impact of these forests on fresh water as well as coastal water was studied by comparing the dissolved organic carbon (DOC) and total dissolved nitrogen (TDN) concentration of a stream and a coastal area within and outside a forested area. Additionally, on the base of a survey, the public opinion towards forests and reforestation projects in Iceland was carried out. The results show that there was significant growth of trees since the last measurement in 2009. However, the stands had a rather low annual CO2-sequestration rate of 0.55 t and 0.74 t per hectare and per year. No differences in DOC and TDN concentrations between water systems within and outside a forested area could be identified. Yet, the vast majority of the local Icelandic residents seems to have a positive attitude towards forests in general and reforestation projects in Iceland, especially in regards to fighting climate change. The understanding of the potential of forests in Iceland and their linkage to water systems as well as the perspective of local residents on Icelandic forests is important in order to manage future large-scale ...